Problem Find the term that is independent of x in the expansion of $\left( 2 + \dfrac{3}{x^2} \right)\left( x - \dfrac{2}{x} \right)^6$.

Answer Key

Solution

For (x - 2/x)^{6}:

$r^{th} \text{ term} = ({^6C_m})(x^{6 - m})\left( -\dfrac{2}{x} \right)^m$

$r^{th} \text{ term} = ({^6C_m})(-2)^m (x^{6 - 2m})$

Let $({^6C_m})(-2)^m = K_j$

For the r^{th} term involving K_{1}x^{0}:

$m = 3$

$K_1 = ({^6C_3})(-2)^3 = -160$

For the r^{th} term involving K_{2}x^{2}:

$m = 2$

$K_2 = ({^6C_2})(-2)^2 = 60$

The constant term in the expansion of (2 + 3/x^{2})(x - 2/x)^{6} is: $K = 2K_1 + 3 K_2 = 2(-160) + 3(60)$

$K = -140$ ← answer

Login No account yet? » Register Can't login? » Reset your password